Chemistry of syn-o,o‘-dibenzene - Gan, Hong; Horner, M. Glenn; Hrnjez, Bruce J.; McCormack, Thomas A.; King, John L.; Gasyna, Zbigniew; Chen, Grace; Gleiter, Rolf; Yang, Nien-chu C. (Journal of the American Chemical Society, 2000)
A new and improved synthesis cis,syn-o,o‘-dibenzene 1 was developed to obtain 1 in larger amounts with improved purity. syn-Dibenzene 1 undergoes thermolysis to two molecules of benzene at a rate slower than that of the thermodynamically more stable anti-dibenzene 2. Kinetic analysis revealed that the higher thermal stability of 1 is due to the higher heat of activation in thermolysis. Photoelectron spectroscopy of 1 showed that the through-bond interaction between the two cyclohexadiene units in o,o‘-dibenzenes is more important than their through-space interaction. A comparative study on the thermolyses of related syn-o,o‘-arene:benzene dimers suggests that thermolyses of syn-o,o‘-arene:benzene dimers proceed via their anti-isomers as an intermediate. syn-Dibenzene 1 also undergoes adiabatic photolysis to one molecule of excited benzene and one molecule of ground-state benzene in good efficiency. The mechanisms of these reactions are discussed.
Gesehen am 03.11.2020